Energy analysis and optimization of inputs for wheat production in Marand region, Iran - JADIDI, MEHRI RAEI; HOMAYOUNIFAR, MASOUD; SABUNI, MAHMOOD SABUHI; MOHAMMADI, ALI (The Indian Journal of Agricultural Sciences, 2012)
The purpose of this study is to determine energy consumption of input and output used in wheat (Triticum aestivum emend Fiori & Paol.)production and to optimize the energy inputs in Marand region, Iran. Data were collected from 150 farmers using a face to face questionnaire. The results revealed that wheat production consumed a total of 37694.6 MJ/ha of which fertilizers was 52.8%, followed by diesel fuel (15.3%). Output-input energy ratio and energy productivity were found to be 2.9 and 0.21 kg/ MJ, respectively. The results of optimization of energy input showed that using existing energy inputs, the yield of wheat can be increased by 32.2% in small farms, 25.5% in medium farms and 6.4% in large farms. Also, the existing level of yield of wheat could be obtained while reducing the total energy inputs by 15.6% in small farms, 5.4% in medium farms and 4.1% in large farms. The results indicated that the rate of forms of direct, indirect, renewable and non-renewable energy have found to be 28.8%, 71.2%, 26.1% and 73.9% of total energy input, respectively.